The relations between personality types and academic achievement: A comparative study of formal and distance education - Bayyurt, Nizamettin; Ergun, Mahmut (Contemporary Research in Education and English Language Teaching, 2023)
The problem of this study is determined by using the psychological personality models and the background of numerous studies on various aspects of the educational achievements of students conducted based on different theoretical approaches. By examining the correlation of cognitive and personality traits and their individual-typical characteristics in the inseparable structure of individuality, and the correlation of these with the educational achievements of students in formal and distance education institutions, the purpose of the study is to examine the effects of personality types on students’ academic achievement. Therefore, a correlation design has been employed in the study. The population of the study is composed of students studying in higher educational institutions in Turkey. The sample of the study, on the other hand, consists of students who receive face-to-face and online education. The data required for the study has been collected by sending survey forms via the Internet. Students from 46 different universities in Turkey participated in the study. To solve the determined tasks and check the initial assumptions, a series of pedagogical research methods were used by utilizing the SPSS program: theoretical analysis of psychological literature in terms of the problem being studied and testing by statistical methods. As a result of these analyses, it has been observed that academic achievement has relations with personality types and students’ success has increased in distance education.